Prospective tools applied to a business valuation model of free cash flow discounted [Herramientas de prospectiva aplicadas a un modelo de valoración de empresas mediante el método de flujo de caja libre descontado] (2019)
The present project intends to establish an activity for the implementation of prospective tools in a business valuation model through the Free Cash Flow (FCL) discounted at the weighted average cost of capital (WACC). It is a company dedicated to the injection of aluminum and they are incorporated into the main tools of the company in the model, constructing valuation scenarios to establish strategies of the entity's management to avoid the materialization of the negative scenarios. © 2019. revistaESPACIOS. com.